High recurrence of device‐related adverse events following transvenous lead extraction procedure in patients with cardiac resynchronization devices. (12th May 2016) - Regoli, François; Bongiorni, Maria Grazia; Rordorf, Roberto; Santamaria, Matteo; Klersy, Caterine; Segreti, Luca; De Regibus, Valentina; Moccetti, Tiziano; Conte, Giulio; Caputo, Maria Luce; Auricchio, Angelo
Abstract: Introduction: Little is known about the clinical outcome and recurring system‐related adverse events (SAE) in cardiac resynchronization therapy (CRT) patients after transvenous lead extraction (TLE). Methods and results: From January 2009 to June 2014, 256 consecutive CRT patients (mean age 68.3 ± 11.6 years, 216 male, 88% in New York Heart Association class II–IV, ejection fraction 35.1 ± 10.8%) were treated at four European institutions with TLE. Indications for TLE included systemic (18%) or local (45%) infection, system malfunction (34%), or other (3%). Demographic, clinical, TLE procedural, and follow‐up data were collected retrospectively. Adverse events (AE) were considered as death from any cause, cardiovascular hospitalization, and SAE (SAE included pocket and/or systemic infection, lead malfunction, or pocket haematoma requiring revision). Complete removal was achieved for 609 out of 614 leads (99.2%) by using either manual traction (28%), mechanical (52%) or laser (20%) sheaths. Over a median follow‐up of 21 (interquartile range 12–29) months, cumulative incidences of any AE and SAE were 53.9% and 21.1%, respectively. Recurring system malfunction occurred in 23 patients (9.0%), infection in 16 patients (6.2%), and pocket haematoma requiring revision in 15 patients (5.9%). Oral anticoagulation therapy was an independent predictor of both any AE [hazard ratio (HR) 2.09, 95% confidence interval (CI) 1.35–3.22, P = 0.001] and SAE (HR 2.38, 95% CI 1.21–4.68, P = 0.012) after TLE. Conclusions: Even though TLE is safe and effective to treat CRT patients, a high burden of recurring SAE after TLE was observed at mid‐term follow‐up. Careful evaluation of both patient characteristics as well as implantation strategy is suggested when indicating TLE in a CRT patient, particularly in patients receiving oral anticoagulation therapy.